2003
DOI: 10.1256/qj.02.174
|View full text |Cite
|
Sign up to set email alerts
|

On a threefold classification of extratropical cyclogenesis

Abstract: SUMMARYA recently proposed extension to the twofold extratropical cyclogenesis classi cation scheme of Petterssen and Smebye is discussed. A third class of extratropical cyclone (type C) is described, in which initial development is controlled by a pre-existing upper-level potential vorticity (PV) anomaly. In its early stages, such a system is indistinguishable from the classical type B cyclone of the Petterssen and Smebye scheme. However, subsequent development cannot be understood in terms of a co-operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…The heating contours in HiGEM can be related to the enhanced low level PV anomaly in HiGEM relative to ERAI. Though it is not possible to attribute causality within the framework of this study, a strengthened low level PV anomaly has been shown to induce stronger low level flow within WCBs (Plant et al 2003). The effect of such enhancement provides a positive feedback to the latent heating.…”
Section: Diabatic Tendencies and Pvmentioning
confidence: 74%
See 1 more Smart Citation
“…The heating contours in HiGEM can be related to the enhanced low level PV anomaly in HiGEM relative to ERAI. Though it is not possible to attribute causality within the framework of this study, a strengthened low level PV anomaly has been shown to induce stronger low level flow within WCBs (Plant et al 2003). The effect of such enhancement provides a positive feedback to the latent heating.…”
Section: Diabatic Tendencies and Pvmentioning
confidence: 74%
“…Latent heat release generates (positive/ cyclonic) PV anomalies below and (negative/anticyclonic) above the location of heating (Hoskins et al 1985;Wernli and Davies 1997). Cyclonic PV anomalies below the heating maxima can act to enhance the low level circulation (Plant et al 2003) and strengthen flow in and downstream of the warm conveyor belt (WCB, Grams et al 2011), a band of ascending moist air responsible for much precipitation in ETCs. Anticyclonic PV generation above the heating maxima can help to slow the movement of the upper level PV maxima (the trough), thus maintaining the vertical tilt of the ETC (Stoelinga 1996), and can also enhance downstream ridging (Davis et al 1993).…”
mentioning
confidence: 99%
“…Davis [1992] and Wernli et al [2006] both showed that the superposition of stratospheric PV anomalies and moisture-induced midlevel PV could enhance cyclone intensity. Finally, Plant et al [2003] showed that midlevel PV anomalies, generated in response to latent heating, were important for the development of two socalled type C cyclones. Type C cyclones are characterised by strong (quasigeostrophic) upper-level forcing, very weak low-level forcing and a vertical upstream tilt that remains constant or increases as the cyclone intensifies [Deveson et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the EKE includes contributions from both cyclones and anticyclones, and it is possible that the role of moisture and latent heating (LH) is more pronounced for certain classes of cyclones (cf. Plant et al 2003) or for deepening rates rather than measures of intensity. LH has been shown to be important for cyclone intensification in theoretical studies (e.g., Emanuel et al 1987), idealized life cycle experiments (Boutle et al 2011;Booth et al 2013;Schemm et al 2013), and various case studies (e.g., Kuo et al 1991;Stoelinga 1996;Ahmadi-Givi et al 2004), but climatologically the role of moisture for the statistical distribution of cyclone intensities is less clear.…”
Section: Introductionmentioning
confidence: 99%